Character Education in Islam: The Role of Teachers in Building Islamic Personality in Elementary Schools - Saepudin, Aep (International Journal of Science and Society, 2023)
Islamic character education in elementary schools plays an important role in shaping students' personalities following religious values. Teachers as central figures in the school environment hold a great responsibility to be role models and guide students spiritually and emotionally. However, there are various challenges teachers face in instilling Islamic character education, both from external factors such as the influence of the social environment, and internal factors such as limited support from parents. This study aims to explore the role of teachers in shaping the Islamic personality of students in elementary schools. The research method used is a qualitative approach, with data collection from various relevant sources such as previous research and scientific articles. The collected data is then processed and analyzed to produce in-depth conclusions regarding the role of teachers in Islamic character education. The conclusion of this study shows that teachers play a key role in shaping Islamic personality through role models, habituation of Islamic values, and spiritual and emotional guidance. The main challenges faced include the negative influence of the social environment and lack of family support. Collaboration between teachers and parents is a critical strategy to increase the effectiveness of Islamic character education. In addition, developing an Islamic school environment and increasing teacher competence also need to be improved. With the implementation of these strategies, Islamic character education can be more effective in forming students who have strong Islamic personalities.